San Luis Obispo Creek Bridge - John H. Klopp::::::photographer::: (1949)
Looking N.W. at Bridge 49-13 old 101 Highway near intersection with New Highway. Dec. 12, 1949. Note sign upper right corner.' Sign in upper right corner reads: 'Visit Reno's Palace Club Oldest in Nevada'